Patterns of Care and Outcomes in Verrucous Carcinoma of the Larynx Treated in the Modern Era - Jayakrishnan, Thejus T.; Abel, Stephen; Interval, Erik; Colonias, Athanasios; Wegner, Rodney E. (Frontiers in Oncology, 2020)
Background: Verrucous carcinoma of the larynx (VCL) is a rare form of laryngeal squamous cell carcinoma. We analyzed the National Cancer Database (NCDB) to examine national treatment pattern, identify factors associated with primary radiation therapy (RT), and compare outcomes in patients with Tis-T2 N0 VCL treated primary surgery and primary RT. Methods: We accessed the NCDB from 2004 to 2015 for patients with Tis-T2 N0 VCL and recorded the treatment modality employed. Multivariable logistic regression was used to identify predictors for radiation therapy. Cox regression was used to calculate hazard ratios for survival. A propensity score matched Kaplan–Meier analysis compared primary surgical treatment to definitive radiation. Results: We identified 732 patients with laryngeal verrucous carcinoma from the NCDB. The majority were cTis-T2 (87%) N0 (96%). We identified 286 vs. 110 Tis-T2N0 patients treated primary surgery and with definitive radiation, respectively, for the purpose of this study. Predictors of radiation were treatment at a community center, no insurance, and higher T stage. Cox regression identified increased age, higher comorbidity score, and government insurance as predictive of worse survival. Propensity matching revealed a trend toward worse survival with definitive radiation, with a median survival of 98 months compared to 143 months (p = 0.02). When including only T1-2 lesions, that is, invasive disease, the trend toward increased survival with surgery [98 months vs. 135 months (p = 0.08)] persisted. Conclusion: The results of the present study support the use of surgery in the management of Tis-T2 N0 VCL when organ preservation is possible.